Ab-initio study of donor-acceptor codoping for n-type CuO - Peng, Yuan (2014)
Single n-type dopant in CuO has either a deep donor level or limited solubility, inefficient in generating free electrons. We have performed ab-initio study of the donor-acceptor codoping to obtain n-type CuO. Our results show that N codoping can slightly improve the donor level of Zr and In by forming shallower n-type complexes (Zr Cu -NO and 2In Cu -NO), but their formation energies are too high to be realized in experiments. However, Li codoping with Al and Ga is found to be relatively easy to achieve. 2Al Cu -Li Cu and 2Ga Cu -Li Cu have shallower donor levels than single Al and Ga by 0.14 eV and 0.08 eV, respectively, and their formation energies are reasonably low to act as efficient codopants. Moreover, Li codoping with both Al and Ga produce an empty impurity band just below the host conduction band minimum, which may reduce the donor ionization energy at high codoping concentrations.